Question
\( \begin{array}{ll}\text { c) } 2^{2 x}-2.2^{x}+1=0 & \text { d) } 2^{2 x+2}-5.2^{x}+1=0 \\ \text { e) } 2^{2 x+1}-2^{x}=0 & \text { f) } 2^{2 x}=2^{2}\left(2^{x}+8\right) \\ \text { g) } 9^{x+1}-10.3^{x}+1=0 & \text { h) } 4^{x}+2^{x}=2^{3+x}+2^{3}\end{array} \)
Ask by Cruz Johnson. in the United Kingdom
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
**Solutions:**
- **c)** \( x = 0 \)
- **d)** \( x = 0 \) and \( x = -2 \)
- **e)** \( x = -1 \)
- **f)** \( x = 3 \)
- **g)** \( x = 0 \) and \( x = -2 \)
- **h)** \( x = 3 \)
Solution
Sure, let's solve each of the given exponential equations step by step.
---
### **Problem c)**
\[ 2^{2x} - 2 \cdot 2^{x} + 1 = 0 \]
**Solution:**
1. **Substitution:** Let \( y = 2^x \). Then \( 2^{2x} = y^2 \).
2. **Rewrite the equation:**
\[ y^2 - 2y + 1 = 0 \]
3. **Factor the quadratic:**
\[ (y - 1)^2 = 0 \]
4. **Solve for \( y \):**
\[ y = 1 \]
5. **Back-substitute \( y = 2^x \):**
\[ 2^x = 1 \]
6. **Solve for \( x \):**
\[ x = 0 \]
**Answer:** \( x = 0 \)
---
### **Problem d)**
\[ 2^{2x+2} - 5 \cdot 2^{x} + 1 = 0 \]
**Solution:**
1. **Simplify \( 2^{2x+2} \):**
\[ 2^{2x+2} = 4 \cdot 2^{2x} \]
2. **Substitution:** Let \( y = 2^x \). Then \( 2^{2x} = y^2 \).
3. **Rewrite the equation:**
\[ 4y^2 - 5y + 1 = 0 \]
4. **Solve the quadratic equation:**
\[ y = \frac{5 \pm \sqrt{25 - 16}}{8} = \frac{5 \pm 3}{8} \]
- \( y = \frac{8}{8} = 1 \)
- \( y = \frac{2}{8} = \frac{1}{4} \)
5. **Back-substitute \( y = 2^x \):**
- For \( y = 1 \): \( 2^x = 1 \) ⇒ \( x = 0 \)
- For \( y = \frac{1}{4} \): \( 2^x = 2^{-2} \) ⇒ \( x = -2 \)
**Answer:** \( x = 0 \) and \( x = -2 \)
---
### **Problem e)**
\[ 2^{2x+1} - 2^{x} = 0 \]
**Solution:**
1. **Factor out \( 2^x \):**
\[ 2^x (2^{x+1} - 1) = 0 \]
- \( 2^x \) is never zero, so set the second factor to zero:
2. **Set \( 2^{x+1} - 1 = 0 \):**
\[ 2^{x+1} = 1 \]
3. **Solve for \( x \):**
\[ x + 1 = 0 \] ⇒ \( x = -1 \)
**Answer:** \( x = -1 \)
---
### **Problem f)**
\[ 2^{2x} = 2^2 (2^{x} + 8) \]
**Solution:**
1. **Simplify the right-hand side:**
\[ 2^2 (2^x + 8) = 4 \cdot 2^x + 32 \]
2. **Substitution:** Let \( y = 2^x \). Then \( 2^{2x} = y^2 \).
3. **Rewrite the equation:**
\[ y^2 = 4y + 32 \]
4. **Rearrange to form a quadratic:**
\[ y^2 - 4y - 32 = 0 \]
5. **Solve the quadratic equation:**
\[ y = \frac{4 \pm \sqrt{16 + 128}}{2} = \frac{4 \pm \sqrt{144}}{2} = \frac{4 \pm 12}{2} \]
- \( y = \frac{16}{2} = 8 \) (valid since \( y > 0 \))
- \( y = \frac{-8}{2} = -4 \) (invalid)
6. **Back-substitute \( y = 2^x \):**
\[ 2^x = 8 \] ⇒ \( x = 3 \)
**Answer:** \( x = 3 \)
---
### **Problem g)**
\[ 9^{x+1} - 10 \cdot 3^{x} + 1 = 0 \]
**Solution:**
1. **Express \( 9^{x+1} \) in terms of base 3:**
\[ 9^{x+1} = 3^{2(x+1)} = 3^{2x + 2} = 9 \cdot 3^{2x} \]
2. **Substitution:** Let \( y = 3^x \). Then \( 3^{2x} = y^2 \).
3. **Rewrite the equation:**
\[ 9y^2 - 10y + 1 = 0 \]
4. **Solve the quadratic equation:**
\[ y = \frac{10 \pm \sqrt{100 - 36}}{18} = \frac{10 \pm 8}{18} \]
- \( y = \frac{18}{18} = 1 \)
- \( y = \frac{2}{18} = \frac{1}{9} \)
5. **Back-substitute \( y = 3^x \):**
- For \( y = 1 \): \( 3^x = 1 \) ⇒ \( x = 0 \)
- For \( y = \frac{1}{9} \): \( 3^x = 3^{-2} \) ⇒ \( x = -2 \)
**Answer:** \( x = 0 \) and \( x = -2 \)
---
### **Problem h)**
\[ 4^{x} + 2^{x} = 2^{3+x} + 2^{3} \]
**Solution:**
1. **Express all terms in base 2:**
\[ 4^x = (2^2)^x = 2^{2x} \]
\[ 2^{3+x} = 2^x \cdot 2^3 = 8 \cdot 2^x \]
\[ 2^3 = 8 \]
2. **Rewrite the equation:**
\[ 2^{2x} + 2^x = 8 \cdot 2^x + 8 \]
3. **Substitution:** Let \( y = 2^x \). Then \( 2^{2x} = y^2 \).
4. **Rewrite the equation:**
\[ y^2 + y = 8y + 8 \]
5. **Rearrange to form a quadratic:**
\[ y^2 - 7y - 8 = 0 \]
6. **Solve the quadratic equation:**
\[ y = \frac{7 \pm \sqrt{49 + 32}}{2} = \frac{7 \pm \sqrt{81}}{2} = \frac{7 \pm 9}{2} \]
- \( y = \frac{16}{2} = 8 \) (valid)
- \( y = \frac{-2}{2} = -1 \) (invalid)
7. **Back-substitute \( y = 2^x \):**
\[ 2^x = 8 \] ⇒ \( x = 3 \)
**Answer:** \( x = 3 \)
---
**Summary of Solutions:**
- **c)** \( x = 0 \)
- **d)** \( x = 0 \) and \( x = -2 \)
- **e)** \( x = -1 \)
- **f)** \( x = 3 \)
- **g)** \( x = 0 \) and \( x = -2 \)
- **h)** \( x = 3 \)
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Mind Expander
For equation \(2^{2x} - 2 \cdot 2^{x} + 1 = 0\), it can be rewritten as a quadratic form by substituting \(y = 2^{x}\). You’ll find \(y^2 - 2y + 1 = 0\) simplifies to \((y-1)^2 = 0\), revealing a double root at \(y = 1\) or \(x = 0\). For the expression \(9^{x+1} - 10 \cdot 3^{x} + 1 = 0\), by letting \(z = 3^x\), the equation reformulates to \(9z - 10z + 1 = 0\), which simplifies to \(9 - 10 + 1 = 0\). This means we are led to a rational framework, allowing us to unearth \(z = 1\), thus \(3^x = 1\) gives \(x = 0\).